Discussion of Inventories and Sales: A Cross Section Study - Grawoig, Dennis E. (Journal of Accounting Research, 1967)
Professors Manes and Samuels have proposed a novel approach to the problem of accounting for inventories. The questions which the paper prompts me to ask merely emphasize the innovative nature of the project. First, let's examine the basic tenets of the study. The authors predicate their paper upon the hypothesis that a major goal for industry should be to minimize the costs associated with inventories. Unless it was thought important or at least worthwhile to consider inventory problems outside of a company's environmental context, an inquiry into inventory policies isolated from other problem and decision areas would be of little interest. It could be argued that cost minimization is never a safe goal. A poor inventory policy might result in an excellent overall strategy. For example, a company might build an excessive inventory, thus incurring a large inventory cost which is nevertheless more than offset by increased sales and goodwill. In other words, excellent inventory policies could be criticized on the basis of suboptimization. Another assumption basic to the study is that the classic operations research inventory model which shows that changes in inventory should vary with the square root of changes in demand is an optimal or at least reasonably strong model, that is, it is worth striving for. It could be argued that the basic, static, deterministic inventory model is not a best model at all. Many experts consider models involving probabilistic demand and/or optimization over a number of periods (dynamic programming) to be more realistic both as to assumptions and objectives. Many of the data problems are recognized by the authors and serve to emphasize the difficulties which they faced in securing meaningful information. There are several additional problems which may exist.